Internalisasi Kaidah Moderasi Beragama Melalui Pendidikan PKn di SMA Negeri 1 Babat Lamongan - Sunardi, Sunardi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
PKn education becomes fundamental in the formation of the character of students through learning within the scope of educational institutions. The selection of appropriate learning strategies aims to achieve learning and reach students, so that it is not interpreted as merely fulfilling the material. Civic Education education should no longer be a monotonous and boring lesson. The learning strategy that can be developed is the strategy for implementing Civics based on religious moderation. From the Civics learning strategy based on Bhineka Tunggal Ika, students are invited to explore and analyze diversity issues in their surroundings. Religious moderation is interpreted as an attitude of tolerance, respect and moderation towards any differences that exist, especially religious differences. Important moderation in religion is applied because Indonesia has a very diverse diversity and the conditions for conflict over these differences. Writing this article aims to present the urgency of the rules of moderation in religion through educational institutions that focus on civics education (PKn) at SMA Negeri 1 Babat with the subject of research as Civics teachers and Class X 2 students. This study uses a descriptive qualitative research model to find the meaning of a phenomenon what happens in society. By using data techniques in the form of interviews and field observations. The results of the study explained that: (1) learning moderation in religion through Civics education based on Bhineka Tunggal Ika is effective in providing national insight and building dialogue about diversity (2) Through Bhineka Tunggal Ika-based projects students are able to apply how to live side by side with an attitude full of love and get along in any difference.